Borneo cave dripwater isotope timeseries resolve the 2009-2012 ENSO cycle - JW, Moerman; K, Cobb; JW, Partin; B, Clark; S, Lejau; J, Malang; AA, Tuen (American Geophysical Union, 2013)
The extent to which changes in El Niño-Southern Oscillation (ENSO) variability have contributed to hydrological changes throughout earth's climate history is poorly constrained by available paleoclimate data. Few records possess the length, resolution, and chronological control to resolve climate variations in the heart of the ENSO region. Results from a recent 5-year daily-resolved timeseries of modern rainfall oyxgen isotopes (delta18O) from northern Borneo -- a region where ENSO has a profound impact on precipitation amount -- show that prominent 6-80/00 interannual rainfall delta18O variations at this site are robustly linked to basin-wide ENSO-driven hydrological changes (Moerman et al., 2013). Thus, stalagmites from Borneo hold immense potential as archives of paleo-ENSO, provided that the large-scale ENSO phenomenon is faithfully translated into dripwater geochemical variations. Here we present the results of a 5-year modern monitoring study of cave dripwater delta18O collected biweekly from three distinct drip sites in northern Borneo caves. All three dripwater delta18O timeseries largely preserve the interannual varability observed in rainfall delta18O, with relatively high delta18O values during the 2009/2010 El Niño event and relatively low delta18O values during the 2010/2011 and 2011/2012 La Niña events. ENSO-related dripwater delta18O variations of up to 50/00 reflect amount-weighted Borneo rainfall delta18O averaged over the preceding 3-9 months. In the case of one drip, however, we find evidence for appreciable contribution from an additional older and well-mixed reservoir with an isotopic composition reflecting mean annual rainfall delta18O, resulting in attenuation of this drip's delta18O signal relative to values predicted by averaged amount-weighted rainfall delta18O alone. These large differences in the amplitude of ENSO-related delta18O variations across our three dripwater timeseries caution against applying a single drip's calibration to stalagmite delta18O records to derive 'absolute' estimates of past precipitation amounts. Our results suggest that ENSO variability has a significant impact on northern Borneo stalagmite delta18O. We demonstrate that changes in ENSO characteristics can drive stalagmite delta18O changes of up to 30/00 on multi-decadal timescales, comparable to the amplitude of recently published stalagmite delta18O reconstructions from our site (Carolin et al., 2013). Overall, this study illustrates the value of monitoring modern water isotope systems to refine and improve interpretations of hydroclimate paleo-proxies.